Pengaruh Instagram terhadap Lifestyle Mahasiswa Antara Realita dan Ekspektasi - Tawazalul Fadilasih; Naya Chelsea Alghany (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the influence of Instagram on college students' lifestyles, focusing on the discrepancy between reality and expectations formed on social media. Instagram has become an important part of college students' lives, not only as a means of communication but also as a medium for constructing self-identity and social image. Through photo and video uploads, many students strive to project an ideal life filled with happiness and success, although this does not always align with reality. This phenomenon gives rise to social pressure, self-dissatisfaction, and a tendency towards a consumerist lifestyle driven by the desire to conform to popular trends. However, Instagram also has a positive side. If used wisely, this medium can be a source of inspiration, learning, and creativity development for students. Therefore, Instagram's influence on college students' lifestyles is largely determined by the user's level of awareness and maturity in balancing the virtual world and real life.